Chat-Based Digital Marketing To Increase Customer Loyalty - Siti Sufaidah; Muhammad Fadil Zulfikar (LPPM Universitas KH. A. Wahab Hasbullah, 2022)
Cooperative is one of the economic business entities that are in an institution that aims to provide services for the employees of the institution. And in the current digital era, systems and applications are an important requirement in running a business that aims to simplify and improve services to members of the cooperative. And it can also minimize errors and can also help store data so that it is easier to find when needed. And cooperative members must also come to the cooperative directly to order or see the stock of goods in the cooperative. Based on these problems, the researchers made an application Chat-Based Digital Marketing To Increase Customer Loyaltyto be implemented in the KH University Cooperative. A. Wahab Hasbullah which aims to create an application that can be used as a tool to simplify and minimize errors or loss of data on stock or goods in the cooperative. Members can check stock of goods and book goods using applications on their respective cellphones without having to come to the cooperative.